Integrating Digital Ethics and Etiquette into Digital Literacy: A Hybrid Learning Framework for Elementary Schools in Indonesia - Anggia Rita Andriana; Imam Khalid (Tuah Foundation, 2026)
This study proposes a hybrid learning framework to integrate digital ethics and etiquette into digital literacy in Indonesian elementary schools. Analysis reveals a gap between contemporary digital literacy concepts, which encompass digital citizenship dimensions, and national curriculum implementation that still focuses on technical aspects. The designed framework consists of three main components: (1) Tiered Content Integration to build self-awareness and responsibility; (2) Synchronization of Online-Offline Methods that connects digital exploration with offline reflection; and (3) Value-Based Contextualization that uses Indonesian local wisdom such as tepo seliro (mutual respect) and gotong royong (cooperation) as its foundation. The research employs a qualitative approach with content analysis of literature, policies, and teaching materials. The findings identify an urgent need for a holistic approach and strategic implications such as enhancing teacher competencies and addressing infrastructure gaps. This framework is expected to help shape a young generation that is not only technologically proficient but also ethical and responsible in the digital ecosystem.